Inequality and Unemployment in Germany: Perception and Reality - Michael Hüther; Judith Niehues (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
Data for the time before the corona pandemic reveal a largely positive picture of the economic and social development in Germany. Most individuals perceived their own situation as very positive, but their views on society are rather pessimistic and overly critical. Contrasting abstract redistributive preferences with prevailing norms of justice reveals further inconsistencies. Thus, it is increasingly unlikely that policymakers can adequately address the concerns and wishes of the population. The pronounced discrepancy between empirical findings on distributional aspects and citizens' perceptions constitutes a veritable problem for democratic processes. That is because this discrepancy is the basis for mistrust between citizens (principals) and politics (agents). Therefore, it becomes increasingly important that politicians explain the logic of their actions in an understandable way. An important prerequisite for more communicable politics is a comprehensive infrastructure for research data that enables politicians, the media, and the public to make valid assessments.
Keywords: D31; D63; P16; 330; Social Justice Norms; Unemployment; Inequality; Perception of Inequality; Political Process